Association of Partial Edentulism with Signs and Symptoms of Temporomandibular Disorders: Partial Edentulism and Jaw Disorders - Malik, Muhammad Imran Ameer; Mumtaz, Maryam; Rana, Muhammad Haseeb; Yaqub, Khalid; Sheryar, .; Hamid, Tayyaba; Naeem, Sajid; Qamar, Khezran (Pakistan Journal of Health Sciences, 2025)
Temporomandibular Joint (TMJ) is a complex joint and occlusal disharmony affects the joint health and result into temporomandibular joint dysfunction syndrome. Objective: To assess the signs and symptoms of temporomandibular joint disorders in partially edentulous patients and find out the association between TMD’s and edentulous span, tooth loss quadrant and occlusal support. Methods: 200 partially edentulous patients selected by non-probability purposive sampling and TMJ were examined for maximum mouth opening, joint deviation, tenderness of muscles of mastication and joint pain with clicking. The sample was grouped into 3 characteristics i.e.; number of partially lost teeth, number of dental quadrants with posterior teeth loss and the numbers of Occlusal Support Zones (OSZ) based on Eichner Classification system. Results: TMJ muscle pain existed in 8.0% and joint pain was 23.0%. Many patients had missing teeth in 2 quadrants 30.0% and had 5-8 numbers of missing teeth 42.5%. A3 support zone was frequently found 29.5%. Significant association of gender was found for TMJ pain, and maximum mouth opening. The tooth loss quadrant, number of partially lost teeth and occlusal support zones had significant association with muscle pain, TMJ pain with clicking and maximum mouth opening. Conclusions: It can be concluded that the partially edentulous patients frequently develop one or more signs and symptoms of TMJ disorders and number of teeth lost, number of quadrants with missing teeth and loss of occlusal support disturb the joint function and associated stomatognathic system.